Quantum mechanical study of the vibrational relaxation of O(2)(+) colliding with Kr - Craimer, M; Pogrebnya, S; Clary, D (1999)
Coupled states calculations on the vibrational relaxation of O+2(υ = 1) colliding with Kr are reported. In the first stage, calculations have been done on single potential energy surfaces and different surfaces have been used. Then treating O+2 as a molecule in a Π ground electronic state, we have performed quantum scattering calculations on the vibrational relaxation on two 1 2A″ and 1 2A′ surfaces. A significant effect due to the inclusion of the second potential surface is reported. A comparison of the calculated rate constants with available experimental data is made. © 1999 American Institute of Physics.